2018
DOI: 10.1002/prep.201700272
|View full text |Cite
|
Sign up to set email alerts
|

Erosivity and Performance of Nitrogen‐Rich Propellants

Abstract: Five propellant formulations were test fired both in a vented vessel and a closed vessel. Two formulations contained 35 % weight of nitrogen‐rich materials. The erosion by weight of the propellants ranged from 0.53 g to 1.31 g after two consecutive test firings of a given propellant. The addition of nitrogen‐rich materials resulted in reduced erosion. Scanning electron microscope and energy dispersive X‐ray spectroscopy revealed nitrogen in the erosion pieces for one of the reference propellants (SB) and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…Figure 9 show that the models fit the data each with a determination coefficient of 0.97 and that the values follow the same trend as the work of Lavoie et al. [35].…”
Section: Resultssupporting
confidence: 75%
“…Figure 9 show that the models fit the data each with a determination coefficient of 0.97 and that the values follow the same trend as the work of Lavoie et al. [35].…”
Section: Resultssupporting
confidence: 75%
“…Additionally, the O content of the TB# steel sample was lower than that of other samples, measuring at 9.16%. This could be attributed to a higher percentage of N 2 in the gas product composition of TB# propellant, which relates to the protective effects of nitrogen, effectively reducing the chemical erosivity of gases at the steel interface. , …”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to a higher percentage of N 2 in the gas product composition of TB# propellant, which relates to the protective effects of nitrogen, 32 effectively reducing the chemical erosivity of gases at the steel interface. 33,34 Figures 6 and 7 6,32 In contrast, as shown in Figure 9e−j, TB#, DB-2#, and NB# propellants resulted in more cracks on the steel surface. The formation of cracks derives from stress generated in a steep temperature gradient 32 and disparate volumes of various iron phases generated in the heat-affected zone.…”
Section: Chemical Compositionmentioning
confidence: 94%
“…22 The experimental results showed that the decomposition products of DHT could accelerate the thermal decomposition process of the propellant components. In addition, the influence of 5,5 0bis(1H-tetrazolyl)-amine (BTA) and 5,5 0 -hydrazine-bistetrazole (HBT) on the thermal decomposition, erosion, and combustion behavior of a typical triple-base gun propellant was also studied, 11,23 and it was found that the propellant containing BTA or HBT showed a lower flame temperature than the gun propellant prepared with the reference formula. At the same time, the burning rate of the gun propellant increased when BTA or HBT was added.…”
Section: Introductionmentioning
confidence: 99%